Pengaruh Penggunaan Jarimatika Terhadap Kemampuan Berhitung Perkalian Peserta Didik Kelas IV Sekolah Dasar - Dewi, Vivi Fitria; Suryana, Yusuf; Hidayat, Syarip (Universitas Pendidikan Indonesia Kampus Serang, 2020)
This study aims to determine the effect of the Jarimatika method on the ability of multiplication in fourth grade of elementary school students.Â This research focused on the use of Jarimatika to assist students in solving numeracy multiplication problem questions. This is based on factual condition where students have not been able to work on the number multiplication and also the monotonous learning methods implemented made learning mathematics feels difficult. This research employed an experimental method with a quasi experimental design in the form of nonequivalent control group design. The experimental group treated by Jarimatika, while the control group used the conventional methods of expository, question and answer and rote method. Data collection techniques in this study used tests. Research data are presented using descriptive statistical data analysis techniques. The research shows that there is an increase in the average of pretest and posttest score of the experimental group. Based on the t-test results obtained, the t obtained value of 6.966 is greater than t table of 2,056 (6,966 2,056) and a significance value of 0,000 is less than 0.05 (0,000 0.05) at a significance level of 5%. Based on the results of the t test, it showed a significant influence on the use of Jarimatika on multiplication learning outcomes in forth grade students of elementary schools.